To evaluate the function \( f(x) = 3 - 2x \) for the given inputs, we can substitute each value of \( x \) into the function:
-
For \( f(0) \): \[ f(0) = 3 - 2(0) = 3 - 0 = 3 \]
-
For \( f(5) \): \[ f(5) = 3 - 2(5) = 3 - 10 = -7 \]
-
For \( f(3) \): \[ f(3) = 3 - 2(3) = 3 - 6 = -3 \]
-
For \( f(2) \): \[ f(2) = 3 - 2(2) = 3 - 4 = -1 \]
Now we can summarize the outputs:
- \( f(0) = 3 \)
- \( f(5) = -7 \)
- \( f(3) = -3 \)
- \( f(2) = -1 \)
The largest output among these values is \( f(0) = 3 \).
Thus, the input that generates the largest output when evaluating the function is 0.